2017
DOI: 10.1002/ajmg.a.38067
|View full text |Cite
|
Sign up to set email alerts
|

The p.R56* mutation in PTHLH causes variable brachydactyly type E

Abstract: Brachydactyly type E is characterized by variable shortening of the metacarpals and/or metatarsals [Temtamy and Aglan, 2008;Mundlos, 2009]. PTHLH is one of the genes associated with this type of brachydactyly, and since its involvement in this trait was discovered [Klopocki et al., 2010;Maass et al., 2010], nine intragenic point mutations [Klopocki et al., 2010;Wang et al., 2015;Jamsheer et al., 2016;Thomas-Teinturier et al., 2016] have been described as causative of BDE with short stature, PTHLH type (OMIM#61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…The BDE PTHLH type was suspected in two patients with BDE and advanced bone maturation for their chronological age. Indeed, two different novel mutations (c.101+ 3delAAGT, in PHP11 [ 34 ] and c.166C>T/p.Arg56*, in PHP12 [ 35 ]) were identified in the PTHLH gene in these patients. The characteristics of these mutations (frameshift and nonsense, respectively) suggested that they were causative of the pathology.…”
Section: Resultsmentioning
confidence: 99%
“…The BDE PTHLH type was suspected in two patients with BDE and advanced bone maturation for their chronological age. Indeed, two different novel mutations (c.101+ 3delAAGT, in PHP11 [ 34 ] and c.166C>T/p.Arg56*, in PHP12 [ 35 ]) were identified in the PTHLH gene in these patients. The characteristics of these mutations (frameshift and nonsense, respectively) suggested that they were causative of the pathology.…”
Section: Resultsmentioning
confidence: 99%
“…(2)(3)(4)(5)10,11,(35)(36)(37) Likewise, PTHrP haploinsufficiency can lead to variable shortening of one or multiple metacarpals and metatarsals, but also to short stature implying that chondrocytes in multiple growth plates undergo accelerated differentiation. (25)(26)(27)(28)(29)(30)(31) It is therefore likely that haploinsufficiency of PTHrP-dependent signaling at the PTHR1 reduces intracellular cAMP levels in growth plate chondrocytes to a similar extent as heterozygous PDE4D, PDE3A, and PRKAR1A mutations, or the reduction of Gsa protein levels through genetic or epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Similar skeletal findings are encountered in patients with mutations in PDE3A , SHOX , or HDAC4 that are associated with different additional abnormalities. Likewise, mutations in PTHLH , the gene encoding PTHrP, lead to shortening of bones in hands and feet, and are usually associated with short stature, but no other clinically apparent defects . Importantly, genetic mutations in GNAS and PRKAR1A (and occasionally in PDE4D ) are associated with readily detectable laboratory abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1; blue text). These molecular defects include translocations [34], microdeletions [35,36], and heterozygous missense, nonstop, or nonsense mutations [35][36][37][38][39].…”
Section: Pthlh Mutationsmentioning
confidence: 99%